BERHAJI PADA MASA ORDE BARU 1966-1998 - Bauwa, Sri Ervikawati; Fitrah, Fitrah; Manay, Helman (Universitas Negeri Gorontalo, 2022)
This study describes how the process of making the pilgrimage during the New Order era 1966-1998. Hajj is the fifth pillar of Islam, which must be done by every Muslim who has the ability both physically, mentally and financially. The results of this study indicate that the process of registering for hajj during the new order was still fairly easy and cheap. In 1997 the hajj fee was only 7,010,000 and at the time of registration until the hajj rituals they were picked up by the bank. At that time the hajj process was still fairly fast with no waiting system, very different from the reformation period where at present there are many hajj candidates which causes the government to carry out a waiting system.